2022
DOI: 10.3844/ajavsp.2022.267.273
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence of Rift Valley Fever and Brucellosis in Cattle of Northern Benin, West Africa

Abstract: Abortive diseases such as Brucellosis and Rift Valley Fever are among the major constraints for ruminant breeding due to the economic losses they cause for the animal keepers and the risk of human and environmental contamination. A serological study was conducted, from August to October 2021, in the commune of Malanville to assess the prevalence of the two diseases in Northern Benin. 92 blood samples were randomly collected from 7 farms that acknowledge abortion occurrence within the last 12 months. The sera r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Omp25 is one of the chief proteins in the OMP class in Brucella spp. Previous studies have reported that Omp25 inhibits TNF-α production in human macrophages infected with B. suis [33]. Previous reports have indicated that the DNA vaccine Omp25 from B. melitensis provides protection against infection with a wild-type virulent strain of B. melitensis in mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…Omp25 is one of the chief proteins in the OMP class in Brucella spp. Previous studies have reported that Omp25 inhibits TNF-α production in human macrophages infected with B. suis [33]. Previous reports have indicated that the DNA vaccine Omp25 from B. melitensis provides protection against infection with a wild-type virulent strain of B. melitensis in mice [34].…”
Section: Discussionmentioning
confidence: 99%